Peginterferon and Entecavir Combination Therapy Improves Outcome of Non–Early Response Hepatitis B e Antigen–Positive Patients. (30th September 2020) - Chen, Lu; Lin, Lanyi; Zhou, Huijuan; Tang, Weiliang; Wang, Hui; Cai, Wei; Bao, Shisan; Guo, Simin; Xie, Qing
Abstract: Background: The efficacy of nucleot(s)ide analogs (NAs) and pegylated interferon (PegIFN) combination therapy for hepatitis B e antigen–positive (HBeAg + ) patients is still controversial. Whether PegIFN and entecavir (ETV) combination therapy could provide a greater benefit for HBeAg + patients was assessed. Methods: Treatment-naïve HBeAg + patients initiated on PegIFN alfa-2a (PegIFNα-2a) for 24 weeks without early response (early response: HBsAg <1500 IU/mL and hepatitis B virus [HBV] DNA <10 5 copies/mL) were recruited in the current study. Among total of 94 patients, 51 were continued on PegIFNα-2a monotherapy, and 43 were offered PegIFNα-2a and ETV combined therapy. Results: Better outcomes in response to the combined therapy, compared with that of the monotherapy, were demonstrated, including more HBsAg decline and loss and HBV DNA decline and HBeAg clearance. Importantly, the patients with HBsAg levels between 1500 and 20 000 IU/mL initially or between 5000 and 20 000 IU/mL after 24 weeks of PegIFNα-2a benefitted more from the combined therapy, compared with those on monotherapy. Conclusions: Combined therapy of PegIFNα-2a and ETV is more efficacious for HBeAg + patients without early response to PegIFN monotherapy, and HBsAg levels are a good predictor of treatment outcomes.